CBN TOOLS FOR HIGH-STRENGTH MATERIALS: SELECTION CRITERIA AND PRACTICAL RECOMMENDATIONS - LUTSIV, IGOR; RADKEVYCH, SVITLANA; KOVAL, YURI; GOLUBOVSKYI, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Machining flat surfaces on parts made from high-strength materials is predominantly carried out using face mills, whose design solutions can differ significantly from one another. A key factor in selecting the tool is the physical and mechanical characteristics of the workpiece material: depending on the method of heat treatment, chemical composition, carbon content, and the presence of alloying elements, hardness and wear resistance can vary considerably. This article presents a modern approach to milling high-strength materials by using cutting tools equipped with cubic boron nitride (CBN). This material is known for its high hardness and thermal stability, making it versatile for cutting various alloys, including cast irons, hardened steels with high hardness, and other high-strength materials subjected to heavy loads. Within the scope of this work, the designs of contemporary face mills and replaceable cutting inserts from leading manufacturers are examined, alongside the optimal cutting parameters that ensure efficient machining with CBN tools. The paper compares offerings from the global cutting-tool market for processing hard-to-machine materials. A review of both domestic and international scientific publications on the wear resistance of cutting inserts revealed that round inserts often exhibit better wear resistance compared to other shapes (such as triangular or square). Advanced developments by major cutting-tool manufacturers - Sandvik Coromant and Seco Tools - are discussed, focusing on the distinctive features of tool design and geometry. The primary emphasis is placed on assessing the efficiency of various face mill and insert configurations when machining high-strength steels (HRC 45+). Alongside theoretical explanations of the advantages of CBN (high hardness, chemical inertness, and heat resistance), the article presents experimental data and test results from real manufacturing conditions. Recommendations are provided for selecting cutting speeds, feeds, and depths of cut for different types of face mills and inserts from Sandvik Coromant and Seco Tools.